Non-Word Repetition in Arabic-speaking children with and without Autism Spectrum Disorder (ASD): A closer look into accuracy and error patterns. - Abd El-Raziq, Muna; Meir, Natalia; Saiegh-Haddad, Elinor (Clinical Linguistics & Phonetics, 2025)
Non-Word Repetition (NWR) tasks effectively identify language impairments and assess phonological skills across diverse populations and languages, including Arabic. Prior research revealed heterogeneity of performance in children with Autism Spectrum Disorder (ASD) on NWR tasks. The current study is the first to evaluate phonological skills of Palestinian-Arabic-speaking children with and without ASD, employing a Palestinian-Arabic NWR task. A total of 142 Palestinian-Arabic-speaking children, aged 5–11 participated in the study, including 75 children with Typical Language Development (TLD) and 67 children with ASD. The NWR task included 18 non-words of varying length (1–4 syllables) and complexity (with and without consonant clusters). Quantitative analysis examined the effects of length and phonological complexity on the NWR accuracy scores in children with TLD and ASD. Error pattern analysis accounting for phoneme and syllable substitutions/deletions/additions and lexicalisations aimed to shed light on the phonological representations of children with and without ASD. Within the ASD group, two subgroups emerged: 72% exhibited age-appropriate NWR performance, while 28% showed performance at-risk for phonological impairment. Non-word length, rather than complexity, significantly influenced the children's performance. Consonant substitution was the most frequent error pattern across all groups. On the theoretical side, these findings extend cross-linguistic evidence of phonological skill heterogeneity in children with ASD to Arabic-speaking children. Additionally, they highlight an overall delayed but qualitatively similar pattern of phonological development in children with ASD. On the clinical side, results underscore the importance of comprehensive language assessment in children with ASD.